(untitled) (Journal of Global Accounting, 2023)
This study examined the effect of cash flow management on financial performance of listed manufacturing firms in Nigeria for a period of ten (10) years covering from 2013-2022. There is lack of consensus among scholars and practitioners about the relationship between cash flows management on financial performance. Panel data were used in this study, which were obtained from the annual reports and accounts of twenty (21) sampled listed manufacturing firms for the period 2013-2022. Ex-Post Facto research design was employed. Inferential statistics using Pearson correlation coefficient, Multicollinearity test, Panel Least Square (PLS) regression analysis and Hausman test were applied to test the hypotheses of the study. The results revealed that abnormal cash flow has a significant and positive effect on cash value added (β1=0.242867; p-value = 0.0000); abnormal production cost has a significant and positive effect on cash value added (β2=0.043125; p-value = 0.0000); of listed manufacturing firms in Nigeria at 5% level of significance respectively. In conclusion, the study found that manipulated cash flows and cost of sales has a significant effect on financial performance of listed manufacturing firms at 5% level of significance. The study recommended amongst others that since cash flows and cost of sales appears to be successful in persuading shareholders to assign higher value to firms with more positive accruals, firms should discretionally utilize them to improve and sustain performance.